Optimization Reading to Learn Learning Model on Narrative Text Writing Skills for Junior High School Students - Yenni Hayati; Ridha Hasnul Ulya; Mira Amazola; Hafrizal Hafrizal; Bima Muhammad Galuh; Ilhami El Husna (STAI Hubbulwathan Duri, 2022)
Educational research is currently more dominated by the development of learning models. However, this has not shown satisfactory results because it tends not to be piloted or disseminated. The purpose of this study is to explain the effect of applying the reading to learn learning model on improving students' narrative text writing skills, especially junior high school students. The sample of this study was the 9th-grade students of SMPN 5 Padang Panjang, totaling 32 students. Data was collected by processing the results of the pretest in the form of performance obtained before the implementation of the reading to learn learning model and the post-test obtained after the implementation of the reading to learn learning model. Data were analyzed using the descriptive analysis method. Based on the results of data analysis, it was found that there was an increase in students' narrative text writing skills before and after the implementation of the reading to learn learning model. This increase can be seen from the number of scores obtained by students regarding the completeness of the narrative text structure from 68 to 89, the completeness of narrative elements from 60 to 75, and the application of EBI from 50 to 72. Therefore, this study can be useful to see the effectiveness of the reading to learn learning model toward students' writing skills and as a way out of writing problems.